77.7k views
2 votes
Y=7x+3 7x-6y=-18 substitution

User Massimobio
by
5.0k points

2 Answers

2 votes

Answer:


y=3


x=0

Explanation:

we have the following system of equations:


y=7x+3\\7x-6y=-18

the substitution method requires that we take one of the variables of one equation, and substitute that value in the other equation.

in this case taking advantage of the fact that in the first equation the value of
y is already cleared, we substitute it in the second equation:


7x-6(7x+3)=-18

and then we solve for x:


7x-42x-18=-18\\-35x-18=-18\\-35x=-18+18\\-35x=0\\x=0

and since x=0 substituting this into the first equation of the system to find the value of
y:


y=7(0)+3\\y=3

the answer is
y=3 and
x=0

User Praful Argiddi
by
5.1k points
7 votes

Answer:

x=0

y=3

Explanation:

y =7x+3 equation 1

7x-6y=-18 equation 2

using equation 1 in equation 2 we have:

7x-6(7x+3)= -18

7x -42x -18 = -18

-35x -18 = -18

-35x = -18 +18

-35x=0

x=0

so we have:

y =7x+3

y= 7(0) +3

y = 3

User John Ptacek
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.